Effect of the porosity, roughness, wettability, and charge of micro-arc coatings on the efficiency of doxorubicin delivery and suppression of cancer cells; Coatings; Vol. 10, iss. 7 - Sedelnikova M. B. Mariya Borisovna; Komarova E. G. Ekaterina Gennadjevna; Sharkeev Yu. P. Yury Petrovich; Chebodaeva V. V. Valentina Vadimovna; Tolkacheva T. V. Tatjyana Viktorovna; Kondranova A. M. Anastasiya Mikhaylovna; Zakharenko A. M. Aleksandr Mikhaylovich; Bakina O. V. Olga Vladimirovna (2020, 2020)
Title screen